Multidisciplinary assessment of vision in children with neurological disability - Lundy, Claire (The Ulster Medical Society, 2011)
INTRODUCTION: There is no consensus as to the best method of assessing vision in children with neurological disability. There are a variety of tests and approaches that can be used. It is important to look at models of assessment that identify the visual diagnosis and provide appropriate feedback and explanation to parents, carers and educational professionals. METHODS: This study reports on the results of comprehensive visual assessments of fifty children with neurological disability over a three year period. It focuses on the feedback from families and professionals after the assessment report was disseminated. RESULTS: The majority of families and professionals strongly agreed that a specialist assessment was needed in this population. Parents and professionals particularly valued the written report which provided guidance on appropriate visual material including advice relevant to education. CONCLUSION: This study highlights the importance of specialist teams engaging with local child development services and indicates how partnership working can potentially be emotionally supportive as well as developmentally beneficial.